Fibrodysplasia Ossificans Progressiva and Pregnancy: A Case Series and Review of the Literature - Alexandra D. Forrest; Danielle M. Vuncannon; Jane E. Ellis; Zvi Grunwald; Frederick S. Kaplan (Case Reports in Obstetrics and Gynecology)
Objective. To evaluate maternal and fetal outcomes in pregnant patients with fibrodysplasia ossificans progressiva (FOP; OMIM#135100), an ultrarare genetic disorder characterized by progressive heterotopic ossification of soft tissues and cumulative disability. Methods. This is a retrospective case series of three patients with FOP who were admitted to Grady Memorial Hospital in Atlanta, Georgia, from to February 2011 to July 2021. Results. Three women delivered preterm infants at our institution. These cases posed unique anesthetic and obstetric technical challenges, particularly when securing the airway and performing cesarean delivery. Importantly, each patient received perioperative glucocorticoids for prevention of further heterotopic ossification. Conclusion. FOP is a unique clinical diagnosis encountered by obstetricians and requires multidisciplinary management for optimal outcomes.